Partai Politik dan Pemilu - Tua Dalimunthe (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
Analysis of Anarchist Politics and Actions, Regional Head Elections, President and Vice President Elections, Political Party Membership, and the role of Political Parties shows the complexity and dynamics in a country's political system. Anarchist actions, although they can reflect people's dissatisfaction with the political system, can also be detrimental to stability and security. Regional head and presidential elections are an important cornerstone of democracy, reflecting the voice of the people, but challenges related to fairness and transparency need to be overcome to ensure the integrity of the democratic system. Membership in a political party plays a crucial role in shaping policies and supporting potential leaders. Then, the role of one political party raises questions regarding political pluralism and alternatives in formulating policies that reflect diverse interests. Therefore, a deep understanding of the relationship between politics, anarchist actions, regional head and presidential elections, political party membership, and the role of a political party, is essential for formulating policies that support inclusive and sustainable democratic dynamics.